Der Glockenspielmord - Rachel L Morgan (Vernacular: New Connections in Language, Literature, & Culture, 2021)
In the city of Munich Germany, diary and journal entries written by an artist named Max Pfeiffer are found, detailing the horrendous way in which he created his first statue for the world-famous Glockenspiel on Marienplatz.